The moral fabric in contemporary societies - Skąpska, Grażyna; Orla-Bukowska, Annamaria; Kowalski, Krzysztof, 1969- (Annals of the International Institute of Sociology. New series, 2003)
The proceedings of the Institute's July 2001 international congress in Krakow, Poland, reflect an interest in reviving morality and ethics to combat the decadent social philosophies of postmodernism and deconstructionism. The 21 papers discuss the moral fabric in contemporary societies, trust in contemporary societies, eastern Europe after Communis.